Analysis of Gyimes Csango population samples on a high-resolution genome-wide basis - Bánfai, Zsolt; Büki, Gergely; Ádám, Valerián; Sümegi, Katalin; Szabó, András; Hadzsiev, Kinga; Erős, Krisztián; Gallyas, Ferenc; Miseta, Attila; Kásler, Miklós; Melegh, Béla (BMC genomics, 2024)
Background The Csangos are an East-Central European ethnographic group living mainly in east of Transylvania in Romania. Traditionally, ethnography distinguishes three Csango subpopulations, the Moldavian, Gyimes and Burzenland Csangos. In our previous study we found that the Moldavian Csangos have East Asian/Siberian Turkic ancestry components that might be unique in the East-Central European region and might help to better understand the history of Hungarian speaking ethnic groups of the area. Since then, we obtained further Csango samples from Moldavia and from a distinct region of Gyimes, which two Csango subgroups are traditionally different since they live in a degree of isolation not only from other people but also from each other. Here we present the first genomic analysis of Gyimes Csangos, which intended to compare the genetic makeup of these two Csango subgroups using both allele-frequency and haplotype-based methods. The main goal of the study was to investigate the genetic isolation of the Csangos on a genome-wide SNP basis and to assess the isolation of Gyimes Csangos, which in contrast to the Moldavians was not yet studied. Results Our results show that these two Csango groups show slight differences from each other. We confirmed the genetic isolation of Moldavian Csangos and revealed that Gyimes Csangos have a similar, but detectably weaker isolation. In the case of Gyimes Csangos we detected also a stronger East European or presumably Asian derived ancestry. Conclusion The Gyimes Csangos show a degree of genetic isolation comparable to that of the Moldavians. The Asian ancestry that differentiates the Moldavian Csango people from the other East-Central European populations may be present in the Gyimes Csangos in an even higher degree, since Gyimes Csango individuals show a more significant share from that ancestry component.